(untitled) (Journal of Humanitarian and Applied Sciences, 2025)
This study aimed to analyze the state of food security of wheat in Libya (2010–2022), employing some approaches to estimate food security indicators. The results revealed food gap, as average domestic wheat production did not exceed 171 thousand tons annually, compared to an average consumption of 940 thousand tons. This led to a low self-sufficiency ratio. The findings also showed significant fluctuations in the food security coefficient, despite its relatively acceptable average level (0.74). The highest values were recorded during (2012–2013), despite political and economic instability following the February 2011 uprising. Conversely, the lowest value (-0.35) was observed in 2022, reflecting the fragility of food security in the face of local and global crises, concluding that achieving safe levels of food security requires enhancing domestic wheat production, establishing a robust national strategic stock to absorb shocks, and diversifying import sources to reduce dependency on a single market.